2008
DOI: 10.1021/bc800356r
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 Click Radiosynthesis and Preclinical Evaluation of a New 18F-Labeled Folic Acid Derivative

Abstract: The folate receptor (FR) is highly expressed on most epithelial cancer cells, while normal cells show only restricted expression of FR. As a result, the FR is an ideal target for receptor-based molecular imaging and therapy of cancer and has become a promising target in oncology. To date, several folate-based chemotherapeutics and imaging probes such as radiopharmaceuticals for single photon emission computed tomography (SPECT) have been developed. However, an (18)F-labeled folic acid derivative suitable for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 44 publications
4
105
0
Order By: Relevance
“…In vitro displacement experiments using KB tumor cells and 3 H-folic acid as radioligand revealed a K i value of 1.8 nM, the highest in vitro binding affinity obtained so far in our group for fluorinated folates (19,20). In vivo PET studies in nude mice found highly specific uptake of 29-18 F-fluorofolic acid in the tumor as well as in the folate receptor-positive kidneys as demonstrated by blockade experiments (Fig.…”
Section: In Vitro and In Vivo Characterizationmentioning
confidence: 53%
See 3 more Smart Citations
“…In vitro displacement experiments using KB tumor cells and 3 H-folic acid as radioligand revealed a K i value of 1.8 nM, the highest in vitro binding affinity obtained so far in our group for fluorinated folates (19,20). In vivo PET studies in nude mice found highly specific uptake of 29-18 F-fluorofolic acid in the tumor as well as in the folate receptor-positive kidneys as demonstrated by blockade experiments (Fig.…”
Section: In Vitro and In Vivo Characterizationmentioning
confidence: 53%
“…In the same assay, folic acid exhibited an inhibitory concentration of 50% of 1.1 6 0.4 nM (K i 5 0.6 6 0.2 nM) (20). The displacement curves of 29-fluorofolic acid and folic acid are depicted in Figure 2.…”
Section: In Vitro Binding Affinity Assaysmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, 18 F-CuAAC is a very attractive strategy for the design and synthesis of radiotracers for molecular imaging purposes. Ross and coworkers used 6-[ 18 F]fluoro-1-hexyne to generate, by click reaction, a folic acid derivative as a promising target molecule in oncology [4]. 18 F-click folate was synthesized by a convenient and efficient two-step radiosynthesis.…”
Section: Introductionmentioning
confidence: 99%